Cosmology in Mirror Twin Higgs and neutrino masses - Zackaria Chacko; Nathaniel Craig; Patrick J. Fox; Roni Harnik (Journal of High Energy Physics, 2017)
Abstract We explore a simple solution to the cosmological challenges of the original Mirror Twin Higgs (MTH) model that leads to interesting implications for experiment. We consider theories in which both the standard model and mirror neutrinos acquire masses through the familiar seesaw mechanism, but with a low right-handed neutrino mass scale of order a few GeV. In these νMTH models, the right-handed neutrinos leave the thermal bath while still relativistic. As the universe expands, these particles eventually become nonrelativistic, and come to dominate the energy density of the universe before decaying. Decays to standard model states are preferred, with the result that the visible sector is left at a higher temperature than the twin sector. Consequently the contribution of the twin sector to the radiation density in the early universe is suppressed, allowing the current bounds on this scenario to be satisfied. However, the energy density in twin radiation remains large enough to be discovered in future cosmic microwave background experiments. In addition, the twin neutrinos are significantly heavier than their standard model counterparts, resulting in a sizable contribution to the overall mass density in neutrinos that can be detected in upcoming experiments designed to probe the large scale structure of the universe.